2012
DOI: 10.4081/oncol.2012.e8
|View full text |Cite
|
Sign up to set email alerts
|

An overview on the role of FLT3-tyrosine kinase receptor in acute myeloid leukemia: biology and treatment

Abstract: Hematopoiesis, the process by which the hematopoietic stem cells and progenitors differentiate into blood cells of various lineages, involves complex interactions of transcription factors that modulate the expression of downstream genes and mediate proliferation and differentiation signals. Despite the many controls that regulate hematopoiesis, mutations in the regulatory genes capable of promoting leukemogenesis may occur. The FLT3 gene encodes a tyrosine kinase receptor that plays a key role in controlling s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
217
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(219 citation statements)
references
References 97 publications
2
217
0
Order By: Relevance
“…The presence of the FLT3 mutation is a poor prognostic factor in AML patients with a high risk of relapse and short duration of remission [1,3,4,8]. In addition, some recent studies emphasize the prognostic importance of the FLT3 allelic burden (allelic ratio); in particular, an allelic ratio higher than 0.5-0.8 could be associated with a negative prognostic effect determined by the mutation [2,8,25,26]. It is noteworthy that, even if all of Figure 2.…”
Section: Transplantation Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the FLT3 mutation is a poor prognostic factor in AML patients with a high risk of relapse and short duration of remission [1,3,4,8]. In addition, some recent studies emphasize the prognostic importance of the FLT3 allelic burden (allelic ratio); in particular, an allelic ratio higher than 0.5-0.8 could be associated with a negative prognostic effect determined by the mutation [2,8,25,26]. It is noteworthy that, even if all of Figure 2.…”
Section: Transplantation Characteristicsmentioning
confidence: 99%
“…The FMS-like tyrosine kinase 3 (FLT3) gene, located on chromosome 13, encodes a tyrosine kinase receptor located on the surface of hematopoietic progenitor cells that is essential for cellular survival and differentiation [1][2][3]. FLT3 mutations can involve the receptor juxtamembrane internal tandem duplication (ITD) domain or the intracellular tyrosine kinase domain (TKD) and can cause, in most cases, an autophosphorylation with the constitutive activation of the receptor, resulting in a higher proliferation and an increased survival of leukemic cells [1,3,4].…”
mentioning
confidence: 99%
“…On the other hand, FLT3 causes the activation of phosphatidylinositol-3-kinase (PI3K) which stimulates protein kinase B or AKT protein that regulates many downstream proteins involve in cell survival and anti-apoptosis. 56 Thus, the inhibition of FLT3 protein expression by CM in the cell lines used in this study might inhibit the activity of PI3K and its downstream effectors to promote cell survival and anti-apoptosis. Previous studies also reported that CM directly inhibited PI3K and anti-apoptotic protein (B-cell lymphoma 2 or Bcl-2) expression.…”
Section: Resultsmentioning
confidence: 87%
“…FLT3-ITD mutation leads to constitutive activation of FLT3 kinase, with subsequent constitutive activation of its downstream signaling pathways including Ras/MAPK kinase pathway, STAT5, and PI3K/Akt pathway (9,10). Moreover, it was also reported that crosstalk between FLT3 and Wnt pathways plays a critical role in the pathogenesis of FLT3-ITD + AML (35,36).…”
Section: Resultsmentioning
confidence: 99%
“…It is associated with worse prognosis and adverse disease outcome (4ā€“7). Mechanistically, FLT3-ITD mutations result in loss of the auto inhibitory function and subsequent constitutive activation of FLT3 kinase as well as its downstream proliferative signaling pathways, including the Ras/MAPK/ERK pathway, STAT5 and PI3K/Akt/mTOR pathway (8ā€“10). Clinically, FLT3-ITD mutations are present in roughly 20% of adult AML cases.…”
Section: Introductionmentioning
confidence: 99%